DISTRIBUTION AND CONTROL METHODS OF PEST INSECTS IN THE SOUTHERN ARAL REGION (Web of Teachers: Inderscience Research, 2025)
This article provides a comprehensive analysis of the main pest insect species found in the Southern Aral region, their impact on agrobiocenoses, and effective control measures against them. The Southern Aral region is one of Uzbekistan’s ecologically sensitive and agriculturally important areas, where climatic conditions and land use practices have led to a sharp increase in insect biomass.